Salience and Online Sales: The Role of Brand Image Concerns - Markus Dertwinkel-Kalt; Mats Köster (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We provide a novel intuition for the observation that many brand manufacturers have restricted their retailers' ability to resell brand products online. Our approach builds on models of salience according to which price disparities across distribution channels guide a consumer's attention toward prices and lower her appreciation for quality. Thus, absent vertical restraints, one out of two distortions – a quality or a participation distortion – can arise in equilibrium. The quality distortion occurs if the manufacturer provides either an inefficiently low quality under price salience or an inefficiently high quality in order to prevent price salience. The participation distortion arises as offline sales might be entirely abandoned in order to prevent prices from becoming salient. Both distortions are ruled out if vertical restraints are imposed. As opposed to the current EU legislation that considers a range of vertical restraints as being hardcore restrictions of competition, we show that these constraints can be socially desirable if salience effects are taken into account.
Keywords: D21; K21; L42; 330; Salience; Online Sales; Antitrust; Vertical Restraints; Distribution Channels